Health seeking behavior among interstate migrant workers in a northern district of Kerala - Ajith V; Mubarack Sani T. P; Nandini G; Jamaludheen C; Nidhun P Krishnan; Ashwin Raj K K; Krishnaraj Rajeev; Sneha Rajan (Global Journal of Medicine and Public Health)
Background